Lenguaje infantil y poesía: «cantan las niñas en alta voz» - García Carcedo, Pilar (Didáctica. Lengua y Literatura, 2004)
The aim of this article is to study the creative components of children language and their relationship with Poetry and poetical resources. As a practical view of this link between poetic language and children language, we show speech samples of two years up to five years old children, and we analyse phenomena as metaphor, paralelism, personification and linguistic creation. Then, Poetry must be one of the essences of teaching and learning in the school and it will allow the growth of the expressive and creative abilities.